Osoblyvosti Pokaznykiv vysokokvalifikovanykh Vesliariv pry Prokhodzhenni Zmahalnoi Dystantsii na Trenazheri "CONCEPT-2" - Omelchenko, O.; Sidak , M. (Physical Education Sports and Human Health, 2020)
The main problem of specialists in the field of physical culture and sports for a long time is to improve the training process of athletes, namely highly skilled rowers in rowing academic. Improving the training process involves finding new tools and techniques that can improve the rower`s athletic performance. This includes improving the various qualities of rowers - strength, strength endurance, special endurance, maximum strength, as well as the functional preparedness and technical qualities of athletes. Improving the rowing process of rowing in academia also involves the use of various tools and techniques, as well as special simulators and devices. These simulators include the "Concept-2" simulator. This simulator allows you to measure the speed of rowing, the power of rowing, the time of passing the distance and the time of passing individual segments of the competitive distance. Purpose: to determine the peculiarities of time, pace and power of highly skilled rowers in rowing at the academic course 2000 m on the simulator "Concept-2". Material and methods: analysis and generalization of scientific and methodological literature, analysis of the passing of the competitive distance on the simulator "Concept-2" (n = 20), methods of mathematical statistics. Results: The results of the analysis of indicators show that when passing the first and fourth segments of the competitive distance, rowing athletes show the best results, while the second and third are the lowest. These data testify to the fact that rowers have a well-developed speed and high-speed strength, but require the development and improvement of qualities such as strength and special endurance. It is established that the need to improve the strength and special endurance of athletes in the construction of the rowing process in rowing academic. Conclusions: The results of the study showed the need to improve the rowing training process in rowing academic using the "Concept-2" simulator.